Postsurgical oral symptoms after insertion of one or two implants for mandibular overdentures: short-term results of a randomized clinical trial - Gabriela Pereira de Resende; Ana Paula Dias; José Luiz Rodrigues Leles; João Antônio Chaves de Souza; Cláudio Rodrigues Leles (SpringerOpen, 2021)
Abstract Objective This randomized clinical trial aimed to compare the short-term postsurgical symptoms after insertion of one or two implants for retention of a mandibular overdenture. This study investigated whether the less invasive single-implant approach results in lower postoperative symptoms compared to the conventional two-implant overdenture. Materials and methods Patients received new complete dentures and were randomly assigned to groups receiving one or two single-stage, early-loaded hydrophilic implants, inserted in the midline (n = 23), or the lateral incisor-canine area bilaterally (n = 24). Patient-reported postoperative symptoms were measured in a 0-100 visual analogue scale concerning pain in the surgical area, pain when chewing, bleeding, swelling, and unpleasantness. Data collection occurred 24 h and 7 and 21 days after surgery. Demographic and clinical features (smoking habit, classification of the residual ridges, and mucosal width and thickness at the implant sites), osteotomy for alveolar bone reduction, and surgery time were tested as predictors of symptom levels. Results Overall reported symptoms were mild and self-limited, with high rates of complete remission after the early loading period of 3 weeks. Progressive improvement of symptoms occurred from the 24-h to the 7-day and 21-day follow-ups (p < 0.001), similarly in both groups. None of the clinical predictors was significantly associated with the changes in symptoms. Conclusions Findings suggest that the insertion of one or two implants may result in similar postoperative outcomes. Clinical relevance The severity of short-term postoperative symptoms may not be a critical factor for the decision between overdenture treatment with one or two implants.